On reserve hoarding in Emes: The case of Turkey - (:unkn) unknown (My University, 2011)
The aim of this paper is to investigate the motives behind the accelerated reserve stockpiling in Turkey. To that end, the paper investigates the long-run equilibrium relationship and Granger causality for the periods of 1974-2009 between international reserves of Turkey and a set of variables put forward by the models of reserve demand. The results of the bounds test for cointegration within the ARDL modelling approach of Pesaran et al. (2001) reveal level relationship between international reserves of Turkey and trade openness, exchange rate volatility, real exchange rate appreciation, financial development, domestic financial development, financial openness, current account volatility, export volatility, public debt, opportunity cost, foreign liabilities and short term debt. Granger causality tests display bidirectional causality between exchange rate volatility and reserves and also unidirectional causality that runs from financial openness, short term debt and domestic financial development to reserves. In addition to the Greenspan-Guidotti rule of short term external debt, the 'Financial-Stability Model' seems to better explain the accelerated demand for reserves in Turkey.
Keywords: Bounds test; Central banks and their policies; Granger causality; International finance; Open economy macroeconomics